PREVENTION STRATEGY OF INCOME SMOOTHING PRACTICES WITH GOOD CORPORATE GOVERNANCE MECHANISM - Purwanti, Rini; Nugrahanti, Yeterina Widi (Jurnal Dinamika Akuntansi, 2016)
The purpose of this study is to investigate the differences of income smoothing based on the number of independent commissioners, the number of audit committee, auditorsâ quality, foreign ownership, managerial ownership, and institutional ownership. The population of this research is manufacturing company listed in Indonesia Stock Exchange (IDX). By purposive sampling, the study got 70 manufacturing companies listed in IDX from 2011 until 2013. Income smoothing was measured by Eckel index. The research used Man-Whitney U test for testing the hypothesis. The result of this research showed that there was no difference of income smoothing based on the number of independent commissioners, the number of audit committee, auditorsâ quality, foreign ownership, and managerial ownership. This study also found that there was difference of income smoothing based on institutional ownership. This study gives advice in order to potential investors who want to invest in a manufacturing company should choose to invest in a manufacturing company that has high institutional ownership. Because from the result of the study, company with high institutional management is proven able to reduce the motivation of the management to take income smoothing action.